Optimizing Channel Structure for Effective Distribution of Petroleum Products in Nigeria - Ayaga, Dennis (British Journal of Marketing Studies, 2019)
The research probed the effectiveness of indirect distribution of petroleum products in Nigeria by the Nigeria National Petroleum Cooperation (NNPC). The study adopted the survey research approach. The method of data collection used was the questionnaire. The Taro Yamane (1967) formula was used in determining the sample size. Benue State was used as the case study. A total of 400 questionnaires were distributed to both motorists who are resident in Benue State and those who drive through the state. Despite spirited efforts, only 359 questionnaires were properly filled, returned and used in the data analysis. Findings revealed that indirect channel structure was effective in the distribution of petroleum products in Nigeria. The result from cross tabulation further showed that indirect distribution of petroleum product was effective in the opinion of both participants who reside in Benue State and those who drive through the state. The research thus recommends that NNPC should sustain the indirect distribution of petroleum products in Nigeria